Continuous exposure to the deterrents cis‐jasmone and methyl jasmonate does not alter the behavioural responses of Frankliniella occidentalis. Issue 1 (12th December 2015) - Egger, Barbara; Spangl, Bernhard; Koschier, Elisabeth Helene
Abstract: Behavioural responses of Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), a generalist, cell sap‐feeding insect species with piercing‐sucking mouthparts, after continuous exposure to two deterrent secondary plant compounds are investigated. We compared in choice assays on bean leaf discs, the settling, feeding, and oviposition preferences of F. occidentalis females that had no experience with the two fatty acid derivatives methyl jasmonate and cis ‐jasmone before testing (naïve thrips) vs. females that had been exposed to the deterrent compounds before testing (experienced thrips). The thrips were exposed to the deterrents at low or high concentrations for varied time periods and subsequently tested on bean leaf discs treated with the respective deterrent at either a low or a high concentration. Frankliniella occidentalis females avoided settling on the deterrent‐treated bean leaf discs for an observation period of 6 h, independent of their previous experience. Our results demonstrate that feeding and oviposition deterrence of the jasmonates to the thrips were not altered by continuous exposure of the thrips to the jasmonates. Habituation was not induced, neither by exposure to the low concentration of the deterrents nor by exposure to the high concentration. These results indicate that the risk of habituation to two volatile deterrent compounds after repeated exposure is not evident in F. occidentalis . This makes the two compounds potential candidates to be integrated in pest management strategies.